Convolutional Neural Network-based Smart Disaster Management Framework for Real-time Detection and Management of Forest Fires - Singh, Kuldeep; Sharma, Eshaan; Baath, Puneet Kaur; Kaur, Kiranbir; Singh, Harminder (International Journal of Sensors Wireless Communications and Control, 2024)
<span class=
Keywords: convolutional neural network